2019
DOI: 10.1002/ceat.201900140
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Steady Operation of a Continuous Pilot Plant for the Di‐Nitration Reaction

Abstract: Continuous‐flow synthesis of the selective herbicide pendimethalin was demonstrated in both a laboratory‐scale and a pilot‐scale reactor using only concentrated nitric acid as nitrating agent. The di‐nitration reaction follows second‐order kinetics where the reaction is first order with respect to both reactant and nitric acid. The pinched‐tube reactor was chosen for pilot‐scale reactor fabrication due to its excellent mixing and mass transfer characteristics compared to a straight‐tube reactor. The estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Validated mass balance and energy balance equations were solved simultaneously to predict the reaction outcome for the proposed capacity and to select the suitable tube diameter for getting the desired heat transfer with predefined product quality. The model predictions showed that ¼-inch SS316 tube is sufficient for achieving the required temperature and product concentration [20]. Also, the model predictions showed that only 500 ml reactor volume was necessary for the desired throughput of 50 kg per day.…”
Section: Determination Of Reaction Kineticsmentioning
confidence: 94%
See 4 more Smart Citations
“…Validated mass balance and energy balance equations were solved simultaneously to predict the reaction outcome for the proposed capacity and to select the suitable tube diameter for getting the desired heat transfer with predefined product quality. The model predictions showed that ¼-inch SS316 tube is sufficient for achieving the required temperature and product concentration [20]. Also, the model predictions showed that only 500 ml reactor volume was necessary for the desired throughput of 50 kg per day.…”
Section: Determination Of Reaction Kineticsmentioning
confidence: 94%
“…), residence time (2-10 min) and temperatures (40-60 °C). The detailed procedure for the measurement and analysis is mentioned in our previous publication [20]. It was found that the reaction follows second order kinetics (Table 1).…”
Section: Determination Of Reaction Kineticsmentioning
confidence: 99%
See 3 more Smart Citations